If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -3x = -3 Solving 10 + -3x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -3x = -3 + -10 Combine like terms: 10 + -10 = 0 0 + -3x = -3 + -10 -3x = -3 + -10 Combine like terms: -3 + -10 = -13 -3x = -13 Divide each side by '-3'. x = 4.333333333 Simplifying x = 4.333333333
| -16x^2+18x+10=0 | | h-h/4+1/4-2h/5-3/5-1 | | 7.5+2.5x=12.5 | | 3x=-2x+4x-24 | | 1/(x-1)+2/(x+1)=6/(x^2-1) | | 4m-8=8 | | -5.5+6.5(1-3s)=-21.5 | | x+7-6x=-33 | | 7b+5=10 | | 5x^2-33x-14= | | 51=-3y | | P/4=p+7/10 | | 9=y+3/4 | | 5+x-3x=3 | | 3x^2-12x^2-36x=0 | | -0.25x+0.5= | | nx+b=7(x-n) | | 1-3.5x=2 | | -14.9+-2.6= | | 55000+1.90x=11x | | 48-x+3=-52 | | 5/6y+1/5(y-6)=(y+1)/4 | | 3/5w=5w+22/25 | | 5x-4(4+5x)=13 | | -130=-6x-6x+2 | | 14x-3=12x+42 | | x^(4/3)-29x^(2/3)+100=0 | | 63/4x9 | | x/3+2-9/6+x/6-1 | | -5f-7+3.5=26.5 | | 6/7y+1/6(y-7)=y+1/7 | | 3x-5/10=7 |